Manajemen komunikasi museum dan pengaruhnya pada kepuasan pengunjung museum sejarah di Bandung - Nuraryo, Imam (Manajemen Komunikasi, 2020)
The purpose of this study was to determine how much influence the management of communication consisting of providing information on national and historical values to museum visitors, maintaining good communication between officers and visitors of the museum, and implementing the etiquette and manners to the satisfaction of the visitors to one of the historical museums of struggle in the city of Bandung.The concept used in this study is the three functions of public relations from Bertrand R Canfield, which have been modified into three functions of communication management of museum services. In addition, this study also uses Service Quality Theory from Parasuraman, Zeithaml and Bery. The research method used was an explanatory survey. Samples taken are the visitors who come to the museum from the 5th (fifth) to the 17th (seventeenth) August 2019.The results of this study indicate that communication management consisting of providing information on national and historical values to museum visitors (X1), maintaining good communication between officers and visitors of the museum (X2), and implementing etiquette and manners in serving museum visitors ( X3) affect the satisfaction of visitors (Y) of 67.2%. While the remaining 32.8% is the influence of other variables not examined.The conclusion is that the management of the museum's communication services to visitors has given satisfaction to its visitors during this period. In addition, it needs to be re-examined what factors can increase museum visitor satisfaction